Aeration of the Human Prussak's Space: A 3D Synchrotron Imaging Study. Issue 7 (August 2021) - Li, Hao; Giese, Dina; Rohani, Seyed Alireza; Zhu, Ning; Ladak, Hanif M.; Agrawal, Sumit; Rask-Andersen, Helge
Abstract : Objectives: Prussak's space (PS) is an intricate middle ear region which may play an essential role in the development of middle ear disease. The three-dimensional (3D) anatomy of the human PS and its drainage routes remain relatively unknown. Earlier studies have histologically analyzed PS, by micro-dissection and endoscopy. Here, we used synchrotron-radiation phase-contrast imaging (SR-PCI), 3D reconstructions, and modeling to study the framework of the human PS, including aeration pathways. It may lead to increased understanding of development of middle ear pathology. Design: Nine human temporal bone specimens underwent in-line SR-PCI at the Canadian Light Source in Saskatoon, Saskatchewan, Canada. Data were processed with volume-rendering software to create 3D reconstructions using scalar opacity mapping and segmentations to visualize its walls in fixed, undecalcified human temporal bones. Results: The PS was found to be an irregular, variably shaped chamber with different aeration systems. Three different drainage pathways were found: 1) via the posterior malleolar pouch of von Tröltsch in seven of nine ears; 2) directly posterior-inferior into the mesotympanum medial to the posterior malleolar pouch in one ear; and 3) anteriorly in another. The posterior-inferior communications depended on the anatomy of the posterior malleolar fold. In one bilateral case, the aeration differed between the ears. Earlier descriptions of upper ventilation routes between the PS and the epitympanic spaces could not be substantiated. Conclusions: The 3D anatomy of the membrane folds organizing the PS in humans was demonstrated for the first time using in-line SR-PCI. The PS was always aerated into the mesotympanum, suggesting its relative independence of attic ventilation. The impact of its various drainage routes on middle ear ventilation and disease were discussed. Abstract : Supplemental Digital Content is available in the text